Life after Digitization, Deschooling Society 2010 & beyond - MAC an AIRCHINNIGH, MICHEAL (My University, 2010)
Schooling may now considered to be an instrinsic part of the society. The term may be taken to cover all those formal institutions established to school young people from approximately the age of 7-11 (primary school), passing through 12-17 (secondary school) until, in the end, 18-21 (tertiary school). The schooling is aided and abetted by the use of prescribed (text)books and the outcome is measured by the formal examination process. Conformity is the norm. Naturally, the young often rebel, in all kinds of different ways. The purpose of the Newspaper is not only to provide ?news? but more significantly to build up a particular view of the society amongst its ?loyal? readership. The edited output is always subject to policy. The Book, on the other hand, is materially and socially different in nature. The time of its making, lasting perhaps a year or more, lends it an authority and offers a sort of cultural world view to its readers. In its guise of textbook it has been the basic foundation of all schooling (and still is). There are books that survive and endure; there are many others that do not. The arrival of the Internet, and then the World Wide Web, and now the multimedia devices that free us from fixed location, all point towards a new social contract between teacher and student, and parent and school. How will the stamp of authority be given to those students who are successful in an Open Schooling Society? In this paper we explore the extent to which the Web has been and can be used to facilitate the upskilling of those who have already been schooled. In particular we focus on the ?hands across the cultural barriers,? linguistic and ideological.
IN_PRESS
Keywords: deschooling society; Dublin Core; Hyperlink; Hypertext; learning web; multimedia; semantic web; technology enhanced learning